Intelligibility and Recognition of Announcer's Speech during Electric Acoustic Conversions in a Transformer - A. Y. Shafranov; T. V. Borbotko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
The purpose of the article is to outline the procedure and the results of the study of the influence of the distance from the sound source to the transformer on speech intelligibility and speaker recognition by voice during electro-acoustic conversion in a transformer. Of all the existing methods for measuring speech intelligibility and voice recognition, the objectified method of articulatory syllabary tables was used. The choice of the method is due to the fact that with a large number of dictated and, accordingly, adopted syllables, the influence of various factors is averaged out. Averaging also occurs if different groups of speakers and auditors take part in the tests. This is the objectivity of the articulatory method. Objective results can also be obtained by using speech to precisely reproduce sound combinations that do not have a semantic load, since when receiving words or phrases, it is possible to think out and restore the elements of the speech distorted by the communication path. The experimental procedure was determined. For the study, a transformer was used as an electroacoustic transducer, and a multifunctional search device ST031M “Piranha” was used as a control and measuring equipment. The selection of speakers and auditors was carried out for the research team. The selection was carried out among men and women between the ages of 18 and 30 who had no obvious speech and hearing impairments and were native speakers of the Russian language. The dependences of the values of the level of speech intelligibility and recognition of the speaker's voice on the distance between the sound source and the transformer are derived. The distances from the sound source to the transformer are determined, at which speech intelligibility corresponds to different quality classes according to GOST 16600-72.